2010
DOI: 10.1021/ed900004y
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Lewis Structures: An Investigation of Student Difficulties in Developing Representational Competence

Abstract: Because Lewis structures provide a direct connection between molecular structure and properties, the ability to construct and use them is an integral component of many chemistry courses. Although a great deal of time and effort has been dedicated to development of “foolproof” rules, students still have problems with the skill. What is more, many students fail to connect the skill with the reasons for learning it. In fact, it appears that conventional instructional practices involved in teaching Lewis structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
233
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(249 citation statements)
references
References 35 publications
10
233
1
5
Order By: Relevance
“…For example, we found that many students (at all levels) were unable to draw Lewis structures [18], despite being given perfectly clear rules about how to do this. By interviewing students and examining their work, it emerged that students did not know why they were learning to draw these structures (i.e., to help them predict chemical and physical properties).…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 94%
“…For example, we found that many students (at all levels) were unable to draw Lewis structures [18], despite being given perfectly clear rules about how to do this. By interviewing students and examining their work, it emerged that students did not know why they were learning to draw these structures (i.e., to help them predict chemical and physical properties).…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 94%
“…As instructors, we want to develop the same experience in our students. Therefore, we aver that representational competence is a critical skill needed for students to develop a sophisticated understanding of college science topics and to succeed in their science courses and future careers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is expected that there will be difficulties in understanding of these concepts [10]. Some studies available in the literature report that the main problem students trying to learn chemistry have is students' failure to learn the basic concepts [12,13,14]. From this point on, the purpose of this study is to examine the preservice chemistry teachers' understanding of periodic table concepts and some atomic properties.…”
Section: Purpose Of the Studymentioning
confidence: 99%